PENGARUH LAMA PERENDAMAN DAN KONSENTRASI ZAT PENGATUR TUMBUH Indole Butyric Acid (IBA) TERHADAP PERTUMBUHAN TUNAS STEK AKAR CENDANA ( Santalum album Linn) PADA MEDIA PASIR - , ANGGAN SUPARIS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sandalwood (Santalum album Linn) is a type of plant which produce timber and sandalwood oil. Since regional autonomy, the amount of sandalwood in South Central Timor regency, East Nusa Tenggara decreased. In 2010, found only 1,426 sandalwood trees with a diameter of 20 cm-100 cm, whereas in 1998 the number reached 112 710 trees. So that needs properly cultivation so sandalwood indwell and able to be a source of economic society. One effort to propagate is by root cuttings. This research to determine the concentration and exact immersion time root cuttings on IBA growth regulator and effects on the growth of sandalwood root cuttings sprout and optimum concentration of plant growth regulators IBA. The study was conducted at the Intensive Silviculture Laboratory, Faculty of Forestry, Gajah Mada University. Materials used are the roots of sandalwood from Wanagama I. The research design use Completely Randomized Design (CRD) factorial with 3 hormone concentration (0 ppm,100 ppm and 300 ppm) and 5 level (10 minutes, 20 minutes, 30 minutes, 40 minutes and 50 minutes). The parameters is initial sprout growth, the amount of sprout, sproutâs height and sprout percentage of live. The results showed that sandalwood can be propagated by using root cuttings. Provision of plant growth regulator IBA for 10 minutes immersion give a fastest average initial sprout growth on day 31, the most average of sprouts amount is 18 sprouts on 10 minutes immersion, highest average sprout is 7.69 cm on 20 minutes immersion, and the largest sprout percentage of live is 66.67% on 20 minutes immersion. The optimum concentration of IBA for initial sprout growth, sprout height, percentage of live is 0 ppm IBA concentration and amount of sprout at 100 ppm IBA concentration. 40 minutes immersion time at 100 ppm IBA concentration has the fastest initial sprout growth on day 28 and the highest sprout number with 23 sprouts on 10 minutes immersion and 300 ppm concentration, the highest sprout is 9.39 cm on 10 minutes immersion with 100 ppm IBA concentration and 83.33 % of the largest life on 10 minutes immersion time with 0 ppm IBA concentration.